2013
DOI: 10.4161/cc.25369
|View full text |Cite
|
Sign up to set email alerts
|

CUL3 and protein kinases: Insights from PLK1/KLHL22 interaction

Abstract: Posttranslational mechanisms drive fidelity of cellular processes. Phosphorylation and ubiquitination of substrates represent very common, covalent, posttranslational modifications and are often co-regulated. Phosphorylation may play a critical role both by directly regulating E3-ubiquitin ligases and/or by ensuring specificity of the ubiquitination substrate. Importantly, many kinases are not only critical regulatory components of these pathways but also represent themselves the direct ubiquitination substrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 36 publications
(57 reference statements)
0
13
0
Order By: Relevance
“…In addition, exome sequencing detected a mutation in the VCAM1 gene, which has been reported to function as a tumor suppressor gene in HCC . Notably, our exome analysis identified mutations in four additional genes, SPOP , KLHL22 , TRPC4AP , and RNF169 , which have been reported to play a role in the ubiquitin pathway . For example, a heterozygous missense mutation altering Ser119 within the SPOP gene was identified in a single HB case (Table ).…”
Section: Resultsmentioning
confidence: 79%
“…In addition, exome sequencing detected a mutation in the VCAM1 gene, which has been reported to function as a tumor suppressor gene in HCC . Notably, our exome analysis identified mutations in four additional genes, SPOP , KLHL22 , TRPC4AP , and RNF169 , which have been reported to play a role in the ubiquitin pathway . For example, a heterozygous missense mutation altering Ser119 within the SPOP gene was identified in a single HB case (Table ).…”
Section: Resultsmentioning
confidence: 79%
“…p.R659Q in ZDHH8 is present in the ExAC data set; rs781662370. ZDHH8 has been reported to be associated with susceptibility to schizophrenia (Mukai et al 2004), ZNF74 has been also reported o be associated with age-at-onset of schizophrenia (Takase et al 2001), and KLHL22 plays a role in ubiquitination (Metzger et al 2013). The WW domaincontaining oxidoreductase (WWOX), a likely tumor suppressor gene, is linked to neuronal development (Chang 2015).…”
Section: Discussionmentioning
confidence: 98%
“…E3 ligase Chfr ubiquitination of Plk1 results in a delay of cells entering mitosis in the presence of mitotic stress through negative regulation of Cdc2 activation (47). Ubiquitination of Plk1 by Cullin 3 ligase complex with the BTB adaptor KLHL22 directs Plk1 dissociation from the kinetochore without affecting Plk1 stability (48, 49). Although CHIP depletion did not affect cell cycle progression during non-stress condition (Fig.…”
Section: Discussionmentioning
confidence: 99%